Substitusi Tepung Ubi Jalar Ungu dan Tepung Tempe pada Bolu Cukke Merupakan Alternatif PMT untuk Ibu Hamil dan Balita - Manjilala Manjilala; Mustamin Mustamin (Jurnal Kesehatan Manarang, 2021)
Supplementary food, especially for vulnerable groups such as pregnant women and toddlers, is one strategy in dealing with nutritional problems, especially during the COVID-19 pandemic. The aim of the study was to determine the acceptability of Bolu Cukke with purple sweet potato flour and tempeh flour substitutes. Experimental research was conducted at the Food Technology Laboratory, Department of Nutrition, Poltekkes, Ministry of Health Makassar with a total of 50 panelists in 2019. The nutritional content was analyzed using the Kjhedal method for protein, gravimetry for fat, and titrimetry for carbohydrates. Acceptance test was analyzed using Kruskal-Wallis and Mann-Whitney test with 95% confidence level. The results showed that the color and aroma of the four sample groups were different (p=0.000 and p=0.028), while there was no difference in texture and taste. Based on the nutritional content, group C had the highest protein content, group A had the highest fat content while group D had the highest carbohydrate content.